Biomarkers in post‐reperfusion syndrome after acute lower limb ischaemia - de Franciscis, Stefano (Int Wound J, 2014)
Ischaemia reperfusion (I/R) injury refers to tissue damage caused when blood supply returns to the tissue after a period of ischaemia. Matrix metalloproteinases (MMPs), neutrophil gelatinase‐associated lipocalin (NGAL) and cytokines are biomarkers involved in several vascular complications. The aim of this study was to evaluate the role of MMPs, NGAL and inflammatory cytokines in I/R syndrome. We conducted an open label, multicentric, parallel group study, between January 2010 and December 2013. Patients with acute limb ischaemia were enrolled in this study and were divided into two groups: (i) those subjected to fasciotomy and (ii) those not subjected to fasciotomy, according to the onset of compartment syndrome. Plasma and tissue values of MMPs and NGAL as well as plasma cytokines were evaluated. MMPs, NGAL and cytokine levels were higher in patients with compartment syndrome. Biomarkers evaluated in this study may be used in the future as predictors of I/R injury severity and its possible evolution towards post‐reperfusion syndrome.